Influence Of Shear Wall on Design Parameter Of Ten Storied Rc Frame Building - VIDYADHARE C V (2011)
INTERNAL GUIDE : Muralidhara EXTERNAL GUIDE:Venkatesh V USN NO : 1MJ10CSE14 CARRIED OUT AT : M V J College Of Engineering Bangalore-67 ACC NO : SE3
Keywords: Influence Of Shear Wall on Design